Susceptibilidad del Enterococcus faecalis ATCC-29212 frente a la combinación de medicamentos antimicrobianos con Hidróxido de Calcio, 2018 - Rodríguez Robalino, Doménica Mishelly (2019)
During the last decade the microorganism Enterococcus faecalis ATCC-29212 has taken significant importance worldwide for its high incidence in different diseases after acquiring resistance to many antimicrobials and even increase after the disappearance of traditional drugs such as Calcium Hydroxide used in endodontic treatments. So this study aimed assess the susceptibility of Enterococcus faecalis ATCC-29212 against the combination of antimicrobial drugs with Calcium Hydroxide. The microorganism was inoculated in 15 Petri boxes with brain heart agar, and two filter paper disc were distributed in T1: Calcium Hydroxide + propylene glycol, T2: Calcium Hydroxide + paramonochlorophenol, T3: Calcium Hydroxide + ampicillin gentamicin + propylene glycol, T4 : Calcium hydroxide + physiological serum. Negative control: distilled water and Positive control: commercial paste based on Calcium Hydroxide in triplicate, inhibition halos were measured and compared with the Duraffourd scale, obtaining higher sensitivity with the treatment 3 of 22.50 ± 3.3. The technique used was observation, measurement and logbook instrument, the results were processed with ANOVA of a factor where it was concluded that the most effective treatment to inhibit the bacterium was Calcium Hydroxide with ampicillin gentamicin and propylene glycol in compared with the other treatments.